"Get the shot, now!" Disentangling content-related and social cues in physician–patient communication. Issue 1 (March 2019) - Brummernhenrich, Benjamin; Jucks, Regina
We investigated how recipients disentangle social and content-related cues in physicians' communication. We presented 53 students with four different statements by physicians concerning the measles-mumps-rubella vaccine. In a 2 × 2 within-subject design, we manipulated politeness and the use of technical terms. We expected politeness variations to mainly affect social perceptions, whereas terminology should mainly affect perceptions of the content. However, politeness did not affect most judgments, whereas terminology influenced more social perceptions than expected. We argue that these variations differentially affect perceptions of fulfillment of basic communion and agency needs. We derive possible implications for physician–patient communication and other contexts.